Toward Cyber Workforce Development: An Exploratory Survey of Information Security Professionals. (September 2018) - Schuster, David; Wu, Steven
High-profile cases of network intrusions in private organizations are becoming a regular occurrence, illustrating the vulnerabilities in current information technology. Cybersecurity is an emerging specialization within information technology careers. Demand for cybersecurity professionals greatly outstrips supply, and the disparity is expected to grow. In this paper, we describe existing efforts to professionalize cybersecurity careers and contribute the results of two exploratory surveys of cybersecurity subject-matter experts (SMEs) working in large corporations in California's Silicon Valley. We asked SMEs about their training and experience, process for threat detection and response, team organization, and major challenges. Our results are the first in a series of studies aimed at bridging the gap between evolving knowledge, skills, and attitudes (KSAs) and the development of training needed to support the cybersecurity workforce.